THE ROLE OF THE FAMILY IN HANDLING STUNTING INCIDENTS IN TODDLERS (CASE STUDY IN KARANGANYAR REGENCY) - Mustain, Mustain; Marni, Marni; Sani, Fakhrudin Nasrul; Yuniarti, Tri (Fakultas Keperawatan, Universitas Klabat, 2025)
Stunting is an unresolved problem to date. In fact, there are still many areas in Indonesia that have quite high stunting rates in toddlers, one of which is in Karanganyar Regency. This study aims to determine the study of the role of the family in handling stunting in toddlers. In answering the research objectives, a phenomenological approach was used which is included in one of the qualitative methods. The sampling technique was carried out purposively, namely in Gebyog Village, Mojogedang District. The sample size in the study was 10 parents who had stunted children in Gebyog Village, Mojogedang District. Qualitative analysis of the research results was also presented using the collaizi method by conducting interviews and making field notes with word-for-word transcripts. Based on the results of the study, it can be seen that the role of parents is mostly at a sufficient level. The results of the study also stated that the nutritional status of most children is at a low level. This is due to the limited economic status of the parents' household so that nutritional intake cannot be met optimally. The results of the study also stated that 4 aspects were identified that were suspected of having an influence, namely perspective and experience, psychological response, parental expectations and moral and material support. Parents' experience in preventing stunting, namely the desire and motivation for stunting to occur. Parents are expected to try to access information related to stunting prevention and apply it in everyday life.